2011
DOI: 10.1115/1.4003236
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigations of a Turbulent Flow Behavior in Isolated and Nonisolated Conical Diffusers

Abstract: In some industrial processes, and especially in agrofood industries, the cleaning in place mechanism used for hydraulic circuits plays an important role. This process needs a good knowledge of the hydrodynamic flows to determinate the appropriate parameters that assure a good cleaning of these circuits without disassembling them. Generally, different arrangements are present in these hydraulic circuits, such as expansions, diffusers, and elbows. The flow crossing these singularities strongly affects the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…As typical hydrodynamic transmission component, hydrodynamic retarders are similar to torque converters in terms of the structure and working principle. So, due to the good performance of the model in adverse pressure gradients along with separating flow and high stability in viscous simulations, the SST model was employed in the steady-state and transient-state analysis (Aloui et al, 2011). No-slip boundary conditions were adopted for viscous flow in the CFD model.…”
Section: Case Study 41 Numerical Modelmentioning
confidence: 99%
“…As typical hydrodynamic transmission component, hydrodynamic retarders are similar to torque converters in terms of the structure and working principle. So, due to the good performance of the model in adverse pressure gradients along with separating flow and high stability in viscous simulations, the SST model was employed in the steady-state and transient-state analysis (Aloui et al, 2011). No-slip boundary conditions were adopted for viscous flow in the CFD model.…”
Section: Case Study 41 Numerical Modelmentioning
confidence: 99%
“…Known under the name of the Q criterion it was proposed by Hunt et al [38]. It can be interpreted by a balance between the rotation rate and the strain rate [39][40]. It should be noted that the distribution of these vortices is different from the infinite medium case.…”
Section: Coherent Structure Criteriamentioning
confidence: 99%
“…Even under laminar flow, flow disturbances are higher for increasing Re. In sudden contraction or expansion sections, the fluid velocity is affected by changing the pipe diameter [134]. Georgantopoulou [128] verified that longer recirculation zones occurred for increasing Re in an abrupt expansion.…”
Section: Fluid Distribution Networkmentioning
confidence: 99%
“…In fact, Simunic et al [44] verified that in dead-end zones, fouling was not affected by fluid flushing (high turbulence from high fluid velocity) that was typical for the main pipe. Several studies identified critical areas for fouling formation such as the regions closed to corners and baffles [59,75,104] and header section [102] in HE, regions closed to expansions/contractions [110,120], angles [128,134], elbows [112,133], and valves [12,114] in distribution networks, and regions closed to corners in the bottom [154], and baffles in the tank wall [165] in STRs. In addition of being prone for fouling phenomena, dead-end zones affect CIP efficacy, compromising the process and product quality, and increase operating and maintenance costs [12].…”
Section: Hydrodynamics On (Bio)fouling Prevention and Controlmentioning
confidence: 99%